1970
DOI: 10.3126/nepjoph.v4i1.5846
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin in clinically-significant macular edema in diabetics with a normal lipid profile

Abstract: Atorvastatin does not affect treatment outcome in CSME with a normal lipid profile over a short term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…A review of clinical trials 7 concluded the improvement of hard exudates with pravastatin, Ozkiris et al 8 conducted a double-blind placebo-controlled trial and concluded that atorvastatin decreased the mean systolic blood pressure in the ophthalmic and central retinal arteries and hence prevents retinopathy progression, a case-control study from USA 9 included 6,441 patients and followed for five years found no association between statins and diabetic retinopathy, a case-series published in Greece 10 observed the improvement of hard exudated and macular oedema. A study assessed the effects of atorvastatin on diabetic retinopathy found no difference between the drug and the placebo arms 11 Nielsen et al 12 in their retrospective study found that statins could prevent retinopathy even before the development of diabetes, another retrospective study from South Korea 13 showed that statins decreased macular oedema and retinopathy. An observational analysis from Japan 14 included 69,070 patients followed for three years found that statins decreased diabetic retinopathy, and a review conducted on statins effect on various eye disorders 15 concluded that statins decreased macular oedema and progression of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…A review of clinical trials 7 concluded the improvement of hard exudates with pravastatin, Ozkiris et al 8 conducted a double-blind placebo-controlled trial and concluded that atorvastatin decreased the mean systolic blood pressure in the ophthalmic and central retinal arteries and hence prevents retinopathy progression, a case-control study from USA 9 included 6,441 patients and followed for five years found no association between statins and diabetic retinopathy, a case-series published in Greece 10 observed the improvement of hard exudated and macular oedema. A study assessed the effects of atorvastatin on diabetic retinopathy found no difference between the drug and the placebo arms 11 Nielsen et al 12 in their retrospective study found that statins could prevent retinopathy even before the development of diabetes, another retrospective study from South Korea 13 showed that statins decreased macular oedema and retinopathy. An observational analysis from Japan 14 included 69,070 patients followed for three years found that statins decreased diabetic retinopathy, and a review conducted on statins effect on various eye disorders 15 concluded that statins decreased macular oedema and progression of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…OCT and hard exudate grading was not done in that study as in our study. 16 Michael Cusick et al showed histopathological evidence of regression of hard exudates and macular edema after reduction of elevated serum lipid levels in dyslipidemic patients. Now-a-days trends are shifting towards use of lipid lowering drugs as primary preventive measure for coronary artery disease in type II diabetics with normal lipid profile.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, treatment with atorvastatin resulted in a 66% reduction in hard exudates and leakage on fluorescein angiography among eyes with DMO and dyslipidaemia [66]. However, it was not found to be beneficial in DR in 30 diabetic subjects with normal serum lipid levels [67]. The combination of atorvastatin and fibrates demonstrated a significant reduction in macular oedema in 47 diabetic patients with non-proliferative DR [68], as well as reducing the rate of recurrent vitreous haemorrhage in eyes with PDR [69].…”
Section: The Blue Mountains Eyementioning
confidence: 99%
“…Corticosteroids represent the mainstay of the treatment. However, steroids are not ideal for long-term therapy because they are associated with a wide array of side effects, particularly increasing total serum cholesterol levels and induction of diabetes and hypertension, thus Narang et al [67] Randomised control trial 30 patients 6 months Atorvastatin No relation between statin use and reduction in hard exudates, macular oedema or visual acuity in subjects with normal serum lipid levels.…”
Section: Uveitismentioning
confidence: 99%